2008
DOI: 10.1016/j.clim.2007.08.013
|View full text |Cite
|
Sign up to set email alerts
|

TNFα blockade in human diseases: Mechanisms and future directions

Abstract: Tumor necrosis factor-alpha (TNFα) antagonists have shown remarkable efficacy in a variety of immune-mediated inflammatory diseases (IMIDs). Therapeutic scope and limitations of these agents are reviewed in a recently published article in the Journal. In spite of their therapeutic popularity, little is known about their modes of action in vivo and factors that limit their scope of therapeutic use. Intriguingly, while all TNFα antagonists including blocking antibodies and soluble receptors are effective in cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
165
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(181 citation statements)
references
References 106 publications
1
165
0
15
Order By: Relevance
“…Partial blockade of CCR5 in T. cruziinfected mice decreased myocarditis without hampering the control of parasite growth ). In the present study, we demonstrated that interfering with the biological effects of TNF-α using Infliximab, an antibody that blocks soluble and membrane-bound TNF-α (Wong et al 2008), led to CCR5 down-modulation and ameliorated heart inflammation without interfering with parasite control. On the other hand, infection of CCR5 -/-mice results in higher parasite burden, mortality, and impaired macrophage and T cell influx into the cardiac tissue (Hardison et al 2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Partial blockade of CCR5 in T. cruziinfected mice decreased myocarditis without hampering the control of parasite growth ). In the present study, we demonstrated that interfering with the biological effects of TNF-α using Infliximab, an antibody that blocks soluble and membrane-bound TNF-α (Wong et al 2008), led to CCR5 down-modulation and ameliorated heart inflammation without interfering with parasite control. On the other hand, infection of CCR5 -/-mice results in higher parasite burden, mortality, and impaired macrophage and T cell influx into the cardiac tissue (Hardison et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, treatment with Etanercept (soluble human TNFR2/p75 that binds TNF-α and lymphotoxin α) aggravated chronic chagasic cardiomyopathy in hamsters, leading to the claim that the absence of TNF-α signaling may be deleterious to the failing heart in Chagas disease cardiomyopathy (Bilate et al 2007). This apparent paradox emphasizes the need for an understanding of the modes of action and the limiting factors of emerging novel therapeutic tools that target TNF-α (Wong et al 2008). Furthermore, TNF-α is involved in cytoprotective signals that prevent and/or delay the development of cardiomyocyte apoptosis (Kurrelmeyer et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the quantitative relationship between the cytokines observed in vitro mimics that observed in the inflamed mucosa in vivo as IL-6, IL-1b, TNF-a and IFN-g are all strongly induced in in vitro by 'activated' PBLs, as well as in colonic biopsies obtained from patients with acute flares of UC. 19 The development of the anti-tumor necrosis factor (TNF) antibodies has revolutionized the management of many chronic-inflammatory diseases and is now an approved treatment for CD, UC, juvenile RA, ankylosing spondylitis, psoriatic arthritis and psoriasis 38,39 However, the mechanisms of their actions are unclear and B10% of patients with 'refractory' or newly diagnosed CD fail to respond to anti-TNF treatment. 40 In normal conditions TNF-a has important roles in the development of the immune system and host protection against infectious pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…1 Three TNF-a antagonists, infliximab, adalimumab and etanercept, the former two being monoclonal antibodies and the latter a soluble receptor, have been licensed for clinical use for the treatment of certain immune-mediated inflammatory diseases since 1998, with the mechanism of neutralizing the excess TNF-a at inflammatory sites. 2 Although these protein-based therapeutics have shown remarkable efficacy, more and more reported adverse responses in patients, and about only 50% or fewer rheumatoid arthritis patients achieved a 50% response in most clinical trials. 2 Side effects, combined with high treatment payments, spur the development of new therapeutic agents for immune-mediated inflammatory diseases.…”
mentioning
confidence: 99%
“…2 Although these protein-based therapeutics have shown remarkable efficacy, more and more reported adverse responses in patients, and about only 50% or fewer rheumatoid arthritis patients achieved a 50% response in most clinical trials. 2 Side effects, combined with high treatment payments, spur the development of new therapeutic agents for immune-mediated inflammatory diseases. Many natural compounds have been found to have the capability of reducing TNF-a levels, so small-molecule natural products with the advantage of a convenient route of administration and the facility of maintaining the production of compounds hold significant promise for a new cost-effective alternative to proteinbased therapeutics.…”
mentioning
confidence: 99%